Pengaruh Pemberian Macam Pupuk Organik dan Volume Penyiraman terhadap Pertumbuhan Bibit Kelapa Sawit di Main Nursery - Saputra, Syahid; Rochmiyati, Sri Manu; Noviana, Githa (Program Studi Agroteknologi INSTIPER, 2025)
A study was conducted from March to May 2025 at KP2 STIPER Yogyakarta Agricultural Institute located in Maguwoharjo Village, Depok District, Sleman Regency, Yogyakarta, to determine effects of organic fertilizer types and watering volumes on growth of oil palm seedlings in the main nursery. The experiment employed a factorial design arranged in a completely randomized design (CRD) with two factors: (1) type of organic fertilizer (vermicompost, chicken manure, and Mucuna bracteata green manure) (2) watering volume (500, 1000, and 1500 mL/day). The data were analyzed using analysis of variance (ANOVA) at a of 5% significant level. The results showed no interaction between fertilizer type and the watering volume on the growth of oil palm seedlings in the main nursery. Providing 500 mL of water was sufficient for the growth of oil palm seedlings in the main nursery. The application of different types of organic fertilizers vermicompost, chicken coops, and green manure had similar positive effects on seedling growth.